Delay tolerant network (DTN) based routing for mobile and hostile environment and its one step ahead - Zhao, Xinxing (2016)
Traditional routings (TRs) such as Ad hoc On-Demand Distance Vector Routing (AODV) or Dynamic Source Routing (DSR) requires the establishment of an end-to-end route from a source to a destination before sending data packets from one node to a next-hop node. However, in some extreme scenarios (e.g., sparse network or in hostile environments), due to unreliable wireless links or no wireless links at all, the pre-established route requirement thus can not be always fulﬁlled. Delay Tolerant Networks (DTN) sometimes is the only or the best alternative in some extreme scenarios, such as in disconnected and/or sparse networks, for DTN has following special characteristics. First, DTN routing does not assume there is a fully connected path from a source to a destination before sending out any data. Secondly, data is forwarded to other mobile nodes in a store-carry-forward approach, that means data can be stored (for certain amount of time, and this time usually much longer than that of in traditional routings) and carried (by relays) and delivered when relays move from one connected part to another connected part of the network. In this way, the data will have a high chance to reach their ﬁnal destination through intermediate relay nodes, given the time is long enough. Node placement is a very important research topic in wireless sensor networks (WSN) and we want to use some of the theories and practices from this ﬁeld as supplements to our DTN networks to advance one more step. As the real deployment area of interests in WSN are usually very wide, and the scattered sensor nodes are placed at strategic points to collect certain information. One of the research problems is that sensor nodes in the area are not always connected, relay nodes might need to be put to bridge the connectivity. So how to provide the whole network connectivity with as small number of relay nodes as possible becomes an interesting question. There are many research works in this area, I will give some details and want to provide a model based on 3-approximation algorithm as supplements to help the DTN networks to be used in wider research and application areas. In this thesis I will describe ﬁrst details about the DTN model I developed and the performances of this model in diﬀerent scenarios in OPNET that support the mobile and hostile environment for a project collaborated with Singapore DSTA; Then I will give the details about the node placement, and base on the 3-approximation algorithm to develop a model which can advance one more step ahead of the DTN networks.